IMPLEMENTASI MANAJEMEN PROFESI DAN KARIER KEPALA SEKOLAH - Perdana, Novrian Satria (Prodi Teknologi Pendidikan, 2017)
Abstract. Burden borne by the Principal in leading his school is not matched by the clarity of the position of Principal which in Permendiknas No. 28 of 2010 states that the principal is a